Environmental Policy and Air Pollution in China Governance and Strategy (Edition 1) - Xu, Yuan (Routledge, 2020)
This book systematically analyzes how and why China has expectedly lost and then surprisingly gained ground in the quest to solve the complicated environmental problem of air pollution over the past two decades. Yuan Xu shines a light on how China's sulfur dioxide emissions rose quickly in tandem with rapid economic growth but then dropped to a level not seen for at least four decades. Despite this favorable mitigation outcome, Xu details how this stemmed from a litany of policy stumbles within the Chinese context of no democracy and a lack of sound rule of law. Throughout this book, the author examines China's environmental governance and strategy and how they shape environmental policy. The chapters weave together a goal-centered governance model that China has adopted of centralized goal setting, decentralized goal attainment, decentralized policy making and implementation. Xu concludes that this model provides compelling evidence that China's worst environmental years reside in the past.This book will be of great interest to students and scholars of Chinese environmental policy and governance, air pollution, climate change and sustainable development, as well as practitioners and policy makers working in these fields.